First record of Crataegus monogyna Jacq. (Rosales: Rosaceae) in Buenos Aires province, Argentina - Segura, Luciano Noel (2014)
Crataegus monogyna Jacq. (Rosales: Rosaceae) is cited and collected for the first time for Buenos Aires province, Argentina. Its distribution is extended within Argentina and southern South America, since it was only known from Río Negro and Neuquén provinces in southern Argentina until now.